PSIKOEDUKASI: GEMAR MENABUNG DENGAN MEMBUAT CELENGAN DARI BOTOL BEKAS - Khasanah, Fitria; Ashari, Anisa Atul Kurnia; Zainu, Handi Mohamad; Setiawan, Rizki; Rahayuningsih, Sri; Oktaviansyah, Aulia Rahman (STKIP PGRI SITUBONDO, 2025)
The implementation of Savings Savings Psychoeducation activities in elementary schools is based on the presence of inorganic waste in the form of plastic bottles, plastic cups, etc. around the school and the lack of student motivation to set aside their pocket money. In this way, the service team had the idea to provide socialization and direct practice on how to use waste in the form of plastic bottles to turn them into savings or piggy banks. The whole series of activities ran smoothly and made the students understand the benefits, purpose and importance of saving for the future, they understood how to save by setting aside pocket money, and the amount of money they had to save every day from the total money they had. Apart from that, students were also invited to develop skills in making piggy banks from used mineral water bottles in groups, and decorate the piggy banks they made as best as possible and as creatively as possible. The best and most creative ones will be given prizes. SDN Kidangbang 1 class 6, SDN Kidangbang 2 class 5 and 6, SDN Kidangbang 3 class 5 and 6, Kidangbang Village, Wajak District, Malang Regency. At that age, students need to get a lot of good and useful knowledge for their growth and development. The method of implementing this activity is carried out in two types of activities, namely socializing the importance of saving through psycho-education to elementary school students and making savings or piggy banks using used plastic bottles. Psychoeducation about people who like to save money by making piggy banks from plastic mineral water bottles was carried out with students at SDN Kidangbang 1, SDN Kidangbang 2, SDN Kidangbang 3 in January 2024. This psychoeducation activity received positive marks from the school community, because this psychoeducation was felt to be fun and very educational for the students. female students at school to prepare them for the future. As a result of this activity, students become more motivated to like saving and students can produce savings or piggy banks according to their individual creativity